Effect of statins on venous thromboembolic events: a meta-analysis of published and unpublished evidence from randomised controlled trials. - Kazem Rahimi; Neeraj Bhala; Pieter Kamphuisen; Jonathan Emberson; Sara Biere-Rafi; Vera Krane; Michele Robertson; John Wikstrand; John McMurray (PLoS Medicine)
Background It has been suggested that statins substantially reduce the risk of venous thromboembolic events. We sought to test this hypothesis by performing a meta-analysis of both published and unpublished results from randomised trials of statins. Methods and findings We searched MEDLINE, EMBASE, and Cochrane CENTRAL up to March 2012 for randomised controlled trials comparing statin with no statin, or comparing high dose versus standard dose statin, with 100 or more randomised participants and at least 6 months' follow-up. Investigators were contacted for unpublished information about venous thromboembolic events during follow-up. Twenty-two trials of statin versus control (105,759 participants) and seven trials of an intensive versus a standard dose statin regimen (40,594 participants) were included. In trials of statin versus control, allocation to statin therapy did not significantly reduce the risk of venous thromboembolic events (465 [0.9%] statin versus 521 [1.0%] control, odds ratio [OR] = 0.89, 95% CI 0.78-1.01, p = 0.08) with no evidence of heterogeneity between effects on deep vein thrombosis (266 versus 311, OR 0.85, 95% CI 0.72-1.01) and effects on pulmonary embolism (205 versus 222, OR 0.92, 95% CI 0.76-1.12). Exclusion of the trial result that provided the motivation for our meta-analysis (JUPITER) had little impact on the findings for venous thromboembolic events (431 [0.9%] versus 461 [1.0%], OR = 0.93 [95% CI 0.82-1.07], p = 0.32 among the other 21 trials). There was no evidence that higher dose statin therapy reduced the risk of venous thromboembolic events compared with standard dose statin therapy (198 [1.0%] versus 202 [1.0%], OR = 0.98, 95% CI 0.80-1.20, p = 0.87). Risk of bias overall was small but a certain degree of effect underestimation due to random error cannot be ruled out. Please see later in the article for the Editors' Summary. Conclusions The findings from this meta-analysis do not support the previous suggestion of a large protective effect of statins (or higher dose statins) on venous thromboembolic events. However, a more moderate reduction in risk up to about one-fifth cannot be ruled out.